Role reversal in apprentices recruiting : which firms search applicant profiles in a targeted way? - Mohr, Sabine [Verfasser]; Ebbinghaus, Margit [Verfasser] (My University, 2024)
"The conventional method of recruiting apprentices, in which firms offer apprentice positions via various media and then wait for incoming applications, is becoming less and less likely to lead to success. One promising remedy is a reversed approach which involves the firms themselves searching applicant profiles in online apprenticeship training exchanges in order to find suitable candidates. This article sheds light on the extent to which this procedure now forms part of recruitment practice of firms." (authors' abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; 370; Betrieb; Personalgewinnung; Bewerberauswahl; Ausbildungsverhalten; BIBB-Qualifizierungspanel